Obsessive–compulsive symptoms are negatively correlated with motor severity in patients with generalized dystonia - Taku Matsuda; Ryoma Morigaki; Yuki Matsumoto; Hideo Mure; Kazuhisa Miyake; Masahito Nakataki; Masafumi Harada; Yasushi Takagi (Scientific Reports, 2022)
Abstract We aimed to clarify the correlations between motor symptoms and obsessive–compulsive symptoms and between the volumes of basal ganglia components and obsessive–compulsive symptoms. We retrospectively included 14 patients with medically intractable, moderate and severe generalized dystonia. The Burke–Fahn–Marsden Dystonia Rating Scale and Maudsley Obsessional Compulsive Inventory were used to evaluate the severity of dystonia and obsessive–compulsive symptoms, respectively. Patients with generalized dystonia were divided into two groups; patients whose Maudsley Obsessional Compulsive Inventory score was lower than 13 (Group 1) and 13 or more (Group 2). Additionally, the total Maudsley Obsessional Compulsive Inventory scores in patients with dystonia were significantly higher than normal volunteers’ scores (p = 0.025). Unexpectedly, Group 2 (high Maudsley Obsessional Compulsive Inventory scores) showed milder motor symptoms than Group 1 (low Maudsley Obsessional Compulsive Inventory scores) (p = 0.016). “Checking” rituals had a strong and significant negative correlation with the Burke–Fahn–Marsden Dystonia Rating Scale (ρ = − 0.71, p = 0.024) and a strong positive correlation with the volumes of both sides of the nucleus accumbens (right: ρ = 0.72, p = 0.023; left: ρ = 0.70, p = 0.034). Our results may provide insights into the pathogenesis of obsessive–compulsive disorder and dystonia.